MEASUREMENT OF THE GAMMA(B-B-OVER-BAR)/GAMMA(HAD) BRANCHING RATIO OF THE Z BY DOUBLE HEMISPHERE TAGGING - Abreu, P; Adam, W; Adye, T; Agasi, E; Ajinenko, I; Aleksan, R; Alekseev, G; Allport, P; Almehed, S; Almeida, F; Alvsvaag, S; Amaldi, U; et al. (1995)
Two measurements of Mathematical expression are presented. Both measurements use 250000 Z decays taken with the DELPHI detector in 1991 and rely mainly on the precision of the microvertex detector. One tagging method is as simple as possible so that background rates can be reliably predicted by simulation. The other one uses a more involved tagging technique and reduces the dependence on simulation as much as possible. Combining both results, Mathematical expression is found to be 0.2209±0.0041(stat.)±0.0042(syst.)±0.0018 Mathematical expression. © 1995 Springer-Verlag.